EFEKTIVITASPENYALURAN DANAUMAT (Magister Manajemen Universitas Wisnuwardhana, 2020)
Al-Falah Social Fund Foundation (YDSF) Malang is one of them in realizing a long-term program by becoming an independent nation, hosting it in its own country and not depending on other nations. Foundation engaged in the collection and distribution of people's funds. Based on the description above, the research focuses are: (1) The most effective program for distributing community funds by YDSF Malang for community empowerment. (2) Implementation of the distribution of community funds collected by YDSF Malang in order to achieve effectiveness. The results of the research explain that the effectiveness of the distribution of funds carried out by YDSF Malang has a high level in terms of measurable quantitative, as well as qualitative, the existence of a multiplier effect and beyond expectation and Improving the quality of mustahik, benefit for others, and the surrounding environment. High effectiveness indicators are determined by the success rate of beneficiaries in managing and using the funds obtained for productive purposes and increasing competence as well as improving the quality of faith, education, and life. Every program initiated has integration with other program ideas